2017
DOI: 10.32738/jeppm.201707.0006
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Project Delivery (IPD) Research Trends.

Abstract: Integrated Project Delivery (IPD) is introduced as a vibrant approach to enhance project implementation, having particular position in recent studies among construction researchers. This study analyzes the research trends on the field of IPD to provide an appropriate vision for future researchers in this specialized field. While so far no comprehensive research has been done in this field, this study provides a comprehensive review of existing studies through in-depth literature review method. This research ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 81 publications
0
33
0
1
Order By: Relevance
“…Legal challenges; issues related to responsibility and insurance are among other challenges of IPD implementation. Current insurances don't fully support delegating responsibility [21,26,36]. Technology, cooperation, and integrated use of technology in IPD implementation are considered as significant steps in its implementation.…”
Section: Ipd Implementation Challengesmentioning
confidence: 99%
“…Legal challenges; issues related to responsibility and insurance are among other challenges of IPD implementation. Current insurances don't fully support delegating responsibility [21,26,36]. Technology, cooperation, and integrated use of technology in IPD implementation are considered as significant steps in its implementation.…”
Section: Ipd Implementation Challengesmentioning
confidence: 99%
“…IPD includes presence of all key factors of the project from outset in an integrated manner, and using their experiences and constructive cooperation in a multilateral contract to have a more successful project and participation in risk and reward for all stakeholders in project life cycle [4] [12]. This technology-driven delivery method has been implemented in a number of projects at various parts of the world [1] [9]. It has been reported that there are certain challenges in adoption and successful implementation of IPD [13]- [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This also has led to distrust among the various stakeholders in the construction sector such as client, consultant, contractor, and suppliers. Integrated Project Delivery (IPD) is an alternate project delivery system that promises to overcome some of the challenges faced in traditional systems [1].…”
Section: Introductionmentioning
confidence: 99%
“…The number of research articles on IPD is generally increasing yearly (Kahvandi et al 2017). However, there is a lack of focus on the effects of IPD in projects.…”
Section: Introductionmentioning
confidence: 99%